DIAGNOSTIC CRITERIA FOR RECONSTRUCTION OF TIDAL CONTINENTAL SHELF REGIMES: CHANGING THE PARADIGM - Jago C.F.; Jones S.E. (My University, 2002)
A biogeochemical flux paradigm is presented which provides a conceptual and numerical framework for reconstructing the dynamical and biogeochemical regimes of ancient tide-driven continental shelves. The paradigm links turbulence, primary production, and suspended particulate matter flux in the water column to microbiological and isotopic proxies in the sediment record and identifies the diagnostic signatures of sediments deposited in stratified, frontal, and mixed dynamic regimes of tidal shelves. The critical governing processes in the water column and at the sediment/water interface are temperature, particulate organic carbon supply, and benthic oxygen consumption, which exhibit strong gradients across tidal mixing fronts. The diagnostic proxies in the sediment record are microplanktonic (e.g. dinoflagellate cysts) and microbenthic (e.g. foraminifera) and their associated stable isotopic properties. Advanced numerical models are available which incorporate biophysical coupling in the water column and benthic boundary layer and which simulate biogeochemical and ecological processes and organic fluxes to the seabed. These models offer potential advances for interpreting microbiological and isotopic proxies of biogeochemical regime preserved in the fine sediment record. Quaternary shelf deposits provide the best potential validation of the biogeochemical flux paradigm since most Quaternary species are living today, but the paradigm is applicable to ancient tidal shelf deposits. The paradigm is particularly applicable to the fine sediment record which potentially preserves the most complete history of shelf evolution.
Keywords: BIOGEOCHEMICAL FLUX; TIDAL SHELF DEPOSITS; FINE SEDIMENTS; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная